2018
DOI: 10.1186/s12913-018-3153-3
|View full text |Cite
|
Sign up to set email alerts
|

RECAPDOC - a questionnaire for the documentation of rehabilitation care utilization in individuals with disorders of consciousness in long-term care in Germany: development and pretesting

Abstract: BackgroundA multitude of different rehabilitation interventions and other specific health care services are offered for individuals with disorders of consciousness in long-term care settings. To investigate the association of those services and patient-relevant outcomes, a specific instrument to document the utilization of those services is needed. The purpose of this study was to develop such a questionnaire administered to caregivers in epidemiological studies or patient registries in Germany.MethodsThe deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…This could be helpful by providing guidance to researchers undertaking the development of RUM instruments, and also by providing insight into the context in which methodological choices behind the current instrument were made. Several previous studies reported the development process of either a disease-specific RUM instrument [ 25 ] or an instrument intended for measuring resource use related to productivity losses [ 27 , 53 ], which limits the generalizability of the process to the development of generic multi-sectoral RUM instruments. In contrast, the current study provides a structured stepwise approach to instrument development based on available best practices [ 2 ] and presents the development process of an instrument that relies significantly less on existing RUM instruments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be helpful by providing guidance to researchers undertaking the development of RUM instruments, and also by providing insight into the context in which methodological choices behind the current instrument were made. Several previous studies reported the development process of either a disease-specific RUM instrument [ 25 ] or an instrument intended for measuring resource use related to productivity losses [ 27 , 53 ], which limits the generalizability of the process to the development of generic multi-sectoral RUM instruments. In contrast, the current study provides a structured stepwise approach to instrument development based on available best practices [ 2 ] and presents the development process of an instrument that relies significantly less on existing RUM instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The growing interest in adopting a societal perspective in economic evaluations calls for appropriate measurement tools that enable measurement of multi-sectoral resource use [23]. There is little existing research on the feasibility, validity and reliability of RUM instruments [3,11,18,19,24], and even fewer studies report the process of instrument development [25][26][27]. This is particularly relevant because the decisions taken during the development process of an instrument, such as the framing and order of the questions, can affect the structure of the instrument and responses to its questions [28].…”
Section: Key Points For Decision Makersmentioning
confidence: 99%
“…A systematic evaluation of patients’ convenient therapy periods could enable therapists to deliver a more personalised and efficient delivery of neurological rehabilitation services [ 68 ]. Consequently, a measurement instrument is needed to assess and address convenient therapy periods in the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive interviews are usually undertaken in rounds, with several participants interviewed and changes to the questionnaire only made after each round. 11 12 Problems in comprehension, recall or response choices to the questionnaire items emerge from the interviews themselves 22 without the interviewer anticipating or having a hypothesis of which items or layout in the questionnaire may require change. Using small tests for change through PDSA cycles, on the other hand, enabled better structuring of questionnaire items with improved ease of comprehension, recall and response choices to items within this questionnaire.…”
Section: Discussionmentioning
confidence: 99%